Influence Characteristics Individual and Competence to Performance with Work Placement as Variable Mediation - Sari, Refinda; Absah, Yeni; Harahap, Hamdani (Riviera Publishing, 2023)
Operations of internal government agencies carry out their respective functions, of course, must pay attention to the performance of their employees, especially for government agencies that are in direct contact with providing services to the community. To be able to provide services to the community, employees must be able to improve their performance. This study aims to analyze the effect of individual characteristics and competencies on employee performance with work placement as a mediating variable for employees of the Medan City Regional Tax and Retribution Management Agency. This type of research is explanatory research with a quantitative approach. The population in this study were 287 employees of the Medan City BPPRD, with a sample of 168 respondents using a purposive sampling technique. Data were analyzed using descriptive statistical analysis and path analysis via IBM SPSS Statistics. The results showed that individual characteristics had a positive effect of ? = 0.045 and 0.042 <0.05 significantly on performance with work placement as a mediating variable. Furthermore, competence has a positive effect of ? = 0.076 and is significant 0.021 <0.05 on performance with work placement as a mediating variable. Individual characteristics and competencies have a positive and significant effect on employee performance with work placement as a mediating variable.